HUBUNGAN DIMENSI KUALITAS PELAYANAN PETUGAS ADMINISTRASI PENGELOLA BPJS KESEHATAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI POLIKLINIK RSUD DR. RASIDIN PADANG - Nilam Devina; Febrian Febrian; Murniwati Murniwati (Faculty of Dentistry Universitas Andalas, 2018)
Administration service of BPJS Kesehatan is the start of whole service of medical service received by every patient. Service quality can be reflected by patients satisfaction after receiving service given by administration officer. Service quality on patients satisfaction is classified into five dimensions of competency, responsiveness, guarantee, emphaty and physical appearance. Dr. Rasyidin General Hospital is a hospital collaborating with BPJS Kesehatan that expected to give a good quality service on medical and non-medical aspects. Increasing public awareness and criticism demand a high quality service to gain the patients satisfaction